2018
DOI: 10.1085/jgp.201711868
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determination of claudin-15 organization and channel selectivity

Abstract: Tight junctions are macromolecular structures that traverse the space between adjacent cells in epithelia and endothelia. Members of the claudin family are known to determine tight junction permeability in a charge- and size-selective manner. Here, we use molecular dynamics simulations to build and refine an atomic model of claudin-15 channels and study its transport properties. Our simulations indicate that claudin-15 forms well-defined channels for ions and molecules and otherwise "seals" the paracellular sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
162
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(183 citation statements)
references
References 75 publications
(164 reference statements)
20
162
1
Order By: Relevance
“…Analysing the water permeability of the channel‐forming proteins claudins‐2, ‐10a, ‐10b and ‐17 revealed that only claudin‐2 is permeable to water, but neither claudin‐10b, although having a similar cation permeability as claudin‐2, nor claudin‐10a or ‐17 are water permeable [for review see]. A molecular dynamics simulation indicated that the claudin‐15 pore is permeable to water . Thus, this study analysed whether or not claudin‐15 acts as a water channel like claudin‐2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysing the water permeability of the channel‐forming proteins claudins‐2, ‐10a, ‐10b and ‐17 revealed that only claudin‐2 is permeable to water, but neither claudin‐10b, although having a similar cation permeability as claudin‐2, nor claudin‐10a or ‐17 are water permeable [for review see]. A molecular dynamics simulation indicated that the claudin‐15 pore is permeable to water . Thus, this study analysed whether or not claudin‐15 acts as a water channel like claudin‐2.…”
Section: Introductionmentioning
confidence: 99%
“…Claudin‐15 was the first claudin of which a crystal structure was solved which was used as basis for molecular channel models of this and other claudins . In recent molecular dynamics (MD) simulation studies, the model of the claudin‐15 channel was refined. The simulations suggests that claudin‐15 forms channels selective for small cations.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids are highlighted in red when acidic and in blue when basic. Arrows marks aspartic acids (D55 and D64), which are found to be important for cation and the water pore function of CLDN15 [11,12,15,16]. Mouse CLDN3 has been classified as a barrier protein and included as a reference.…”
Section: Transcript Levels and Response To Salinitymentioning
confidence: 99%
“…Cldns are integral membrane proteins with 4 trans-membrane domains and two extracellular loops (ECL). The amino acid residues of the first ECL are critical for the permselectivity of the junction they create in homo-or hetero-dimeric and -tetrameric combinations [13][14][15][16]. There are 27 claudins (CLDNs) paralogs described in mammals [12]; in the teleost lineage, an extensive expansion of the cldn gene family due to gene duplications has led to a higher number with e.g., 56 in Fugu [17] and 54 in zebrafish [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation